Developing an intelligent tool for computer-assisted formulaic language learning from YouTube videos. Issue 2 (24th May 2022) - Lin, Phoebe
Abstract: This paper presents IdiomsTube (https://www.idiomstube.com ), the first-ever computer-assisted language learning tool for facilitating the learning of English idiomatic expressions from YouTube videos. The web-based tool is designed to automatically (1) assess the speech rate and lexical difficulty level of any learner-chosen English-captioned YouTube video; (2) generate a range of vocabulary-building and revision tasks (e.g. fill-in-the-blanks, the classic spelling game hangman, pronunciation, flashcards); and (3) recommend YouTube videos based on learners' individual learning progress, class teachers' instructions, and current trends. This paper describes the app's current features in conjunction with the challenges endemic in the development of applications that automatically generate English language learning content out of internet video content. At the time of writing, the IdiomsTube app had over 8, 000 registered users worldwide.